Analysis of Quality Control of Bread Products Using the Seven Tools Method and Kaizen in Banana Bread Shop Jombang - Khakiki, Elin Ken; Donoriyanto, Dwi Sukma (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
Banana Bread Shop Jombang is a micro company engaged in the food industry by producing sweet bread with various variants. However, in the production process there are still defects in the product, there by reducing the quality of the bread production. The purpose of this study was to minimize defects in Mexican chocolate bread products produced by Banana Bread Shop Jombang by conducting an analysis using the seven tools and kaizen methods in the production process. The data collection technique used was interview, observation and documentation methods during March-May 2023. The results of the analysis showed that the types of defects that occurred in Mexican chocolate bread products were non-standard forms, burnt, flat, and cut by the packaging machine. Based on the four types of disability, flat is the most dominant with a total of 2.198 pcs. The occurrence of defects in mexico chocolate bakery products is caused by 5M factors: man, methods, machines, materials, and milieu. Improvements made to minimize the occurrence of defects in Mexican chocolate bread are by implementing the kaizen method.